Modeling and Simulation of Skill Decay at the Organizational Team Level. (September 2017) - Trani, Alexandra N.; Hutto, Clayton J.; Fausset, Cara B.; Cheng, Samuel; Hale, Chris R.; McDermott, Thomas; Folds, Dennis J.
When building teams, organizations select individuals capable of acquiring and maintaining skills required for team success. Often, teams undergo a period of skill non-use that can result in skill decay during the lifespan of the team. Despite this reality, researchers have failed to create a comprehensive model that can predict complex skill decay at multiple levels within an organization. McDermott and colleagues (2016) proposed an equation to address this gap. Using simulation data, the present paper applies this equation to model expected skill decay in three hypothetical contexts: simple, mid-range, and complex engineering design cases. The model predicts team-level skill decay in a holistic manner by integrating factors from task, environment, and team characteristics. Results indicate that, while novel for its integration mechanisms, the model maintains strong congruency with previous literature for individual factors. We discuss ways that organizations may reduce complex skill decay as well as future research directions.